Increased angiogenesis seems to correlate with inferior overall survival in myeloid sarcoma patients - Piccaluga, Pier P.; Paolini, Stefania; Navari, Mohsen; Etebari, Maryam; Visani, Giuseppe; Ascani, Stefano (Polish Journal of Pathology, 2018)
Myeloid sarcomas (MS) are tumors composed by myeloid elements and developing outside bone marrow. The prognosis is overall poor, only stem cell transplantation being consistently reposted as a potentially curative approach. In this study we explored whether microvessel density, a biomarker of angiogenesis, might be relevant in MS. We studied 60 MS, 24 acute myeloid leukemia, 5 normal bone marrow samples and 2 cases of extramedullary hemopoiesis in patients without evidence of hematological malignancy. We used immunohistochemistry (anti-CD34) to identify and quantify micro-vessel density (MVD) and micro-vessel grading (MVG). We found that MS had significantly higher MVD and MVG than normal bone marrow (p = 0.0002 and p < 0.001, respectively). We then found that cases with monocytic morphology had significantly higher MVD than myelo-monocytic and blastic ones (p = 0.005), while no differences were recorded based on extramedullary site. Finally, we found that higher MVD and higher MVG were associated with inferior outcome in terms of overall survival in multivariate analysis (p = 0.05 and p = 0.02, respectively), when censoring for stem cell transplantation was undertaken. In conclusion, we documented for the first time that increased angiogenesis is characteristic of MS and correlates with survival, suggesting that anti-angiogenic approaches might deserve a clinical evaluation in this setting.